Community Quality-of-Life Indicators: Best Cases VII - Holden, Meg; Phillips, Rhonda; Stevens, Chantal (Springer International Publishing : Imprint: Springer, 2017)
This book is the seventh volume in a series covering best practices in community quality of life indicators. The case studies and analysis in this volume demonstrate how community indicators projects today operate within a need to amplify the voice of disadvantaged communities, seriously explore the increasing use of information technology, produce positive community change and sustain these efforts over time. The work presented here spans North American and Australian community work and demonstrates how the field of community indicators has undergone a rapid evolution in only a few decades. Today as in their original formulations, community indicators projects are designed to gauge the social, economic and physical health and well-being of communities. .
Keywords: Social sciences.; Leadership.; Medical research.; Public administration.; Quality of life.; Social service.; elektronické knihy; electronic books